P4HA2 promotes tumor progression and is transcriptionally regulated by SP1 in colorectal cancer - Xuening Dang; Xiaojian Chen; Zhonglin Liang; Zhujiang Dai; Wenjun Ding; Jinglue Song; Jihong Fu (Cancer Biology & Therapy)
P4HA2 has been implicated in various malignant tumors; however, its expression and functional role in colorectal cancer (CRC) remain poorly elucidated. This study aims to investigate the involvement of P4HA2 in CRC metastasis and progression, uncovering the underlying mechanisms. In colorectal cancer (CRC), P4HA2 exhibited overexpression, and elevated levels of P4HA2 expression were associated with an unfavorable prognosis. Functional assays demonstrated P4HA2‘s regulation of cell proliferation, and epithelial–mesenchymal transition (EMT) both in vitro and in vivo. Additionally, the AGO1 expression was correlated with P4HA2, and depletion of AGO1 reversed the proliferation and EMT function induced by P4HA2. Chromatin immunoprecipitation (ChIP) and luciferase assays suggested that the transcription factor SP1 binds to the promoter sequence of P4HA2, activating its expression in CRC. This study unveiled SP1 as a transcriptional regulator of P4HA2 in CRC and AGO1 is a probable target of P4HA2. In conclusion, P4HA2 emerges as a potential prognostic biomarker and promising therapeutic target in colorectal cancer.